Semiconductors: Interface Design Principles for High‐Performance Organic Semiconductor Devices (Adv. Sci. 6/2015) - Nie, Wanyi (Adv Sci (Weinh), 2015)
Organic solar cells (OSCs) are a promising cost‐effective candidate in next generation photovoltaic technology. However, a critical bottleneck for OSCs is the electron/hole recombination loss through charge transfer state at the interface, which greatly limits the power conversion efficiency. In article number 1500024, W. Nie, A. Mohite, and co‐workers demonstrate a simple strategy of suppressing the recombination rate by inserting a spacer layer at the donor‐acceptor interface, resulting in a dramatic increase in power conversion efficiency. [Image: see text]